Antibacterial, Antioxidant and Cytotoxic Properties of Crinum asiaticum Bulb Extract - Rahman, Md Atiar; Sharmin, Rumana; Uddin, Md Nazim; Rana, Md Sohel; Ahmed, Nazim Uddin (Bangladesh Journal of Microbiology, 2012)
Antibacterial effect of Crinum asiaticum bulb extract (1mg/disc) was tested on four Gram- positive and six Gram-negative bacteria by disc diffusion method using kanamycin (30 ìg/disc) as standard antibiotic disc. The bulb extract (250-1000mg/disc) showed significant zone of inhibition against all Gram-positive and Gram-negative bacteria ranging from 12-14 mm in diameter. Antioxidant potential of the same extract was evaluated by 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging method. The extract showed remarkable free radical scavenging effect (95.96%) providing the IC50 value of 5.62 for the bulb extract and 5.46 for ascorbic acid (standard antioxidant) at the concentration of 1000 ìg/ml. The bulb extract was found to be (LC50 value 94.06 ?g/ml) in Brine-Shrimp lethality test. DOI: http://dx.doi.org/10.3329/bjm.v28i1.11801 Bangladesh J Microbiol, Volume 28, Number 1, June 2011, pp 1-5